EFEKTIVITAS ORGANISASI BADAN PENDAPATAN DAERAH DALAM PENGELOLAAN PAJAK PARKIR DI KOTA SEMARANG - Diyah Ayu Pangestuti; Maesaroh Maesaroh (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
Local tax is dues/contribution that must be done by institution or individual without balanced reward to finance for local government organization and local development. Tax is imposed to people by government. It is a policy from government so it needs to maintain so that the policy can give fair charge in line with tax system of Indonesia. From the aspect of Locally-Generated Revenue, parking tax revenue is one of revenues or Locally-generated revenue of Semarang. As known that parking is type of service business that has close relation and mutual support with world trade that generates local revenue. Parking becomes one of means to support national budget, so that local government determines parking tax. This research aims to fine out effectiveness of parking tax revenue toward locallygenerated revenue in Semarang in 2016-2017. This research is conducted in Income Office Region of Semarang. Collecting the data is conducted by requesting report on realization of locally-generated revenue and parking tax of Semarang in 20162017.